Pengaruh Perubahan Kondisi DAS terhadap Debit Sungai Studi Kasus DAS Waduk Jatigede - Kodoatie, Robert Johannes (MEDIA KOMUNIKASI TEKNIK SIPIL, 2020)
Changes in land use in the upstream of Jatigede watershed cause discharge and sedimentation problems in the Jatigede Reservoir. The objective of this study is to analyse the affect of land use changes in the Jatigede Reservoir watershed to the inflow and sediment to the reservoir. SCS Curve Number method and HEC-HMS modeling system are used to discharge analysis. Flood discharges in the reach of Cimanuk River close to the reservoir using data of 2009 are Q2=1,751.5 m3/sec, Q5=2,280 m3/sec, Q25=3,064.5 m3/sec, Q50=3,589 m3/sec. Flood discharges in the reach of Cimanuk River close to the reservoir using data of 2018 are Q2=2,053.8 m3/sec, Q5= 2,616.7 m3/sec, Q25 = 3,439.2 m3/sec, Q50=3,984.9 m3/sec. Discharges increase in 10 years (based on 2009 data and 2018 data). For example discharge increment for Q25 is 375 m3/sec. The increment is due to the increment of CN number as the consequences of land use changes. In other words along with the time, flood discharge in the rainy season increases, however discharge in the drought season decreases.